The Decline of the Labor Share is not Explained by the Capitalization of Intellectual Property Products - Simcha Barkai (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2021)
The U.S. labor share has clearly been declining since the early 1980s. This does not depend on whether or not we capitalise intellectual property products. Koh, Santaeulàlia-Llopis and Zheng (2020) approximate the labor share by a single linear time trend over the entire period of 19292019. This period includes a long period of time over which the labor share is known to be mostly stable and a shorter period of time over which the labor share is known to decline. Once we separate out the period starting in the 1980s we recover the decline in the labor share.
Keywords: 330